Mothers' perceptions about the nutritional status of their overweight children: a systematic review - Caliandra Francescatto; Natalia S. Santos; Vanessa F. Coutinho; Roberto F. Costa (Elsevier, 2014)
Objective: this systematic review aims to explore and describe the studies that have as a primary outcome the identification of mothers' perception of the nutritional status of their children. Sources: the PubMed, Embase, LILACS, and SciELO databases were researched, regardless of language or publication date. The terms used for the search, with its variants, were: Nutritional Status, Perception, Mother, Maternal, Parents, Parental. Summary of the findings: after screening of 167 articles, 41 were selected for full text reading, of which 17 were included in the review and involved the evaluation of the perception of mothers on the nutritional status of 57,700 children and adolescents. The methodological quality of the studies ranged from low to excellent. The proportion of mothers who inadequately perceived the nutritional status of their children was high, and was the most common underestimation for children with overweight or obesity. Conclusion: despite the increasing prevalence of obesity in pediatric age, mothers have difficulty in properly perceiving the nutritional status of their children, which may compromise referral to treatment programs. Resumo: Objetivo: esta revisão sistemática tem por objetivo explorar e descrever os estudos que apresentam como desfecho primário a identificação da percepção das mães quanto ao estado nutricional de seus filhos. Fonte dos dados: foram utilizadas as bases de dados PubMed, Embase, LILACS e SciELO, sem distinção de idioma ou data de publicação. Os termos utilizados para a busca, com suas variações, foram: Nutritional Status, Perception, Mother, Maternal, Parents, Parental. Síntese dos dados: após triagem dos 167 artigos encontrados, restaram 41 artigos para leitura do texto completo, sendo incluídos 17 artigos, que envolveram a avaliação da percepção de mães sobre o estado nutricional de 57.700 crianças e adolescentes. A qualidade metodológica dos artigos variou de baixa a excelente. A proporção de mães que percebiam inadequadamente o estado nutricional dos filhos foi elevada, sendo mais comum a subestimativa para crianças com sobrepeso ou obesidade. Conclusão: apesar do aumento da prevalência de obesidade em faixas pediátricas, as mães têm dificuldade de perceber adequadamente o estado nutricional de seus filhos, o que pode comprometer o encaminhamento para programas de tratamento. Keywords: Nutritional status, Perception, Mother, Maternal, Parents, Parental, Palavras-chave: Estado nutricional, Percepção, Mãe, Materno, Pais, Parental